Synthesis and Characterization of Al(III) Complex of 1,3,5-Hexahydrocyclophosphazene - VASHISTHA, ATUL; JADON, S.P.S. (Asian Journal of Chemistry, 2010)
The reaction product of (NPCl2)3 with Al(III) chloride was synthesized and its characterization, are being reported herewith with the help of mass, IR and EPR spectra, assigning its dimeric nature of the complex as Al(N3P3H2)3.